1980
DOI: 10.1017/s0305004100057534
|View full text |Cite
|
Sign up to set email alerts
|

Tripos theory

Abstract: One of the most important constructions in topos theory ia that of the category Shv (A) of sheaves on a locale (= complete Heyting algebra) A. Normally, the objects of this category are described as ‘presheaves on A satisfying a gluing condition’; but, as Higgs(7) and Fourman and Scott(5) have observed, they may also be regarded as ‘sets structured with an A-valued equality predicate’ (briefly, ‘A-valued sets’). From the latter point of view, it is an inessential feature of the situation that every sheaf has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 6 publications
(10 reference statements)
1
149
0
Order By: Relevance
“…In contrast, full induction principles, for example Ind, hold for arbitrary formulas, or equivalently for arbitrary subclasses of the domain. Such principles are expressed 15 I am grateful to Peter Aczel for pointing this out to me. 16 Various simpler formulations of Infinity are possible in the presence of the Exp, Pow or Sep axioms.…”
Section: Infinity and Inductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, full induction principles, for example Ind, hold for arbitrary formulas, or equivalently for arbitrary subclasses of the domain. Such principles are expressed 15 I am grateful to Peter Aczel for pointing this out to me. 16 Various simpler formulations of Infinity are possible in the presence of the Exp, Pow or Sep axioms.…”
Section: Infinity and Inductionmentioning
confidence: 89%
“…15 Because of this, we follow Lawvere and turn primitive recursion into the defining property of the natural numbers: 16 Infinity (Inf ) N is a set, 0 ∈ N , s ∈ N N and, for every set A, element z ∈ A, and function f ∈ A A , there exists a unique function h ∈ A N satisfying: h(0) = z and h(s(x)) = f (h(x)) for all x ∈ N .…”
Section: Infinity and Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main examples of this construction are localic toposes and realizability toposes obtained from a tripos, see [HJP80,Pit02,vO08].…”
Section: Proposition For An Elementary Doctrinementioning
confidence: 99%
“…Hyland, P.T. Johnstone and A.M. Pitts, see [HJP80] and which made apparent the abstract construction behind Higg's complete Heyting valued toposes and toposes obtained from Kleene's realizability like the effective topos, see [Hyl82]. In [MR15,Pas15b] it was shown that the tripos-to-topos construction T P of a given tripos P : C op G G Heyt can be obtained as the exact completion of the doctrine P cx : Prd P op G G Heyt obtained by freely completing the original tripos with full comprehensions and comprehensive diagonals.…”
Section: Introductionmentioning
confidence: 99%